Fear of COVID-19: the mediation role between the COVID-19 diagnosis and KAP in Spanish university students - Ana Cancela; Mar González-Noriega; Ana Visiers (BMC, 2023)
Abstract Background Although health public services recommend prevention strategies for COVID-19 some of these recommendations have not been taken seriously by young people. Understanding why some people comply with these recommendations and others do not seem to be crucial in helping public health services to predict behavior and compliance with rules, especially for young people. Previous studies suggest that knowledge, attitudes, and practices (KAP) are useful to assess compliance with the preventive measures and public health policies. Being afraid has also been found to correlate with more engagement with preventive measures. This study aims to assess the KAP and fear of COVID-19 of Spanish university students and to understand the relation between diagnosis, KAP and the level of fear. Method Participants of this cross-sectional study were 598 college students (69.4% women) from different Spanish Universities. Data were collected for a month using an online questionnaire through Sphinx iQ2. Results Levels of KAP among Spanish students were satisfactory and results suggest the presence of fear among them. More importantly, fear of COVID-19 mediated the impact of the diagnosis on the KAP. Conclusions Feeling fear seems to be the mechanism underlying the relationship between diagnosis and KAP. Diagnosis is associated with KAP when the diagnosis it is accompanied by measures of fear. KAP, diagnosis, or perceived fear of COVID must be taken together in consideration for health interventions and public health campaigns design.